Теплообмен при охлаждении высокотемпературной поверхности диспергированной водой - Переселков, Александр Романович (НТУ "ХПИ", 2009)
The method and results of investigations of dependence between specific heat and heat temperature surface irrigation density have been presented. The influence of parameters which determine hydrodynamic conditions of surface irrigation has been investigated
Keywords: тепломер; теплосъем; теплообмен; натекающие капли